Percentagewise presence of judging scores in the European, World Championships and Olympic Games in the Men`s Artistic Gymnastics from 2006 to 2011 year - Atikovic, A. (Journal of Physical Education and Sport, 2013)
The main goal of this paper is a comparison of the percentagewise presence of the scores by the quality levels from the C.I. competition. Establishment of the differences between certain apparatus, competitions and judges` commissions stems from the set goal. There is a big difference in the variability of results at Olympic Games, World and European Championship. Generally, the lowest average score at the competitions was on the pommel horse, and the highest one, on the vault. The article can provide useful information on the role of tactics in gymnastics competition in the team and all around competition.